2016
DOI: 10.1186/s13068-016-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure-oriented substrate specificity engineering of aldehyde-deformylating oxygenase towards aldehydes carbon chain length

Abstract: BackgroundAldehyde-deformylating oxygenase (ADO) is an important enzyme involved in the biosynthetic pathway of fatty alk(a/e)nes in cyanobacteria. However, ADO exhibits quite low chain-length specificity with respect to the substrates ranging from C4 to C18 aldehydes, which is not suitable for producing fuels with different properties or different chain lengths.ResultsBased on the crystal structures of cADOs (cyanobacterial ADO) with substrate analogs bound, some amino acids affecting the substrate specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…8. It has been shown in previous studies that the ligand approaches the diiron cluster from opposite side of the His-148 residue with its headgroup binding directly to the Fe2, which is the preferred iron for substrate binding (21,35). We also observed similar interactions in the case of the Np-ADO at 300 K where ligand appeared to be bound to the Fe2 (Fig.…”
Section: Protein Engineering For Improved Thermostability Of Adosupporting
confidence: 84%
See 1 more Smart Citation
“…8. It has been shown in previous studies that the ligand approaches the diiron cluster from opposite side of the His-148 residue with its headgroup binding directly to the Fe2, which is the preferred iron for substrate binding (21,35). We also observed similar interactions in the case of the Np-ADO at 300 K where ligand appeared to be bound to the Fe2 (Fig.…”
Section: Protein Engineering For Improved Thermostability Of Adosupporting
confidence: 84%
“…The role of cysteine residues has been investigated in ADO from Nostoc punctiforme PCC 73102, and it was shown that Cys-71 is involved in maintaining the activity, structure, and stability of ADO (39). Certain amino acid residues present in the vicinity of the substrate channel were identified for successfully changing the substrate chain length selectivity of ADO (21). The ADO belongs to the nonheme dinuclear iron oxygenase family of enzymes that includes methane monooxygenase, type I ribonucleotide reductase, and ferritin (3, 35, 40 -42).…”
mentioning
confidence: 99%
“…The importance of rationally designing enzyme libraries with amino acid diversity in specific regions has also been recently demonstrated in a variety of examples that involve optimization of substrate access tunnels of enzyme active sites to improve activity and stability . Several computational tools have been generated for identifying and engineering substrate access tunnels for diverse applications in enzyme engineering, including altering substrate selectivity (see references within a recent review).…”
Section: Design Methods For Improving Directed Evolution Of Protein Amentioning
confidence: 99%
“…The reaction is dependent on an external reducing system to provide altogether four electrons for the (i) activation of the di-iron center for oxygen binding, (ii) hemiacetal radical formation, and (iii) generation of the product complex ( Paul et al, 2013 ; Rajakovich et al, 2015 ). Characteristically, ADO has relatively broad substrate specificity towards different aldehydes, with the highest activity towards the native linear C16 and C18 precursors ( Khara et al, 2013; Bao et al, 2016 ; Zhang et al, 2016 ). This feature is accompanied by a low apparent catalytic turnover rate with reported k cat values below 0.02 s −1 in different contexts in vitro and in vivo ( Khara et al, 2013; Andre et al, 2013; Bao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristically, ADO has relatively broad substrate specificity towards different aldehydes, with the highest activity towards the native linear C16 and C18 precursors ( Khara et al, 2013; Bao et al, 2016 ; Zhang et al, 2016 ). This feature is accompanied by a low apparent catalytic turnover rate with reported k cat values below 0.02 s −1 in different contexts in vitro and in vivo ( Khara et al, 2013; Andre et al, 2013; Bao et al, 2016 ). Kinetic characterization has also revealed that the affinity towards the aldehyde substrates is poor, especially for the shorter precursors, with K M values in the millimolar range ( Bao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%